Assessment of water quality using Canadian Water Quality Index and GIS in Himreen Dam Lake, Iraq - Lazem, L.F. (Mesopotamian Journal of Marine Sciences, 2022)
The Canadian versions of Water Quality Index (WQI) and Geographical Information Systems (GIS) were applied in this study to assess the water quality of Himreen Dam Lake. Water samples were taken seasonally during the period from summer 2014 to spring 2015. A total of 10 parameters were measured in this work, and were considered in calculating the water quality index (WQI), namely: potential hydrogen ion (pH), electrical conductivity (EC), total dissolved solid (TDS), sodium (Na+), calcium (Ca+2), magnesium (Mg+2), chloride (Cl-), sulphate (SO4-2), nitrate (NO3) and sodium adsorption ratio (SAR). The results showed that the pH was ranged from 7.1-7.9, EC was varied from 558-864 µS/cm and TDS was ranged between 322-522 mg/l. The ranges of sodium, calcium, magnesium, chloride, sulphate, nitrate and sodium adsorption ratio were 13-34 mg/l, 32.27-86.34 mg/l, 35.0-67.8 mg/l, 29-88 mg/l, 129-254 mg/l, 0.9-3.6 µg N-NO3/l and 1.62-4.99 meq/l respectively. The values for the water quality index (WQI) were varied from 72.14 to 72.36 that categorized within category three (fair). The lowest value was recorded at station 2 while the highest was encountered from station 1. The results revealed that the quality of Himreen Lake water was suitable for irrigation.